Educação para política do Estado Novo (1937-1945): um estudo do conceito e dos objetivos educacionais na revista Cultura Política - Prado, Adonia Antunes (1982)
In this study we inteded to expose and discurs a part of the dominant thought during period of the 'Estado Novo' (1937-1945): the educational thought. This study was based on articles of the Cultura Política review from where we emphasize the analysis of the ideology and its political aspects. The methodology of this work was based on the analysis of the articles, content which had the education as the diseussion objects. The importance of those articles is linked to the fact that Cultura Política review was one of the most representative vehicle of the dominant thought and the ideology of the public intelligentzia. The analysis and the discution of the empyrical data show us that the education was conceived has a tools for achieving social objvectives but not necessarily educational. It was observed that the stablishment used the educational resources to achieve politicals goals. It was one of the most important aspects we achived analysis. Thouse politicals goals are most clearly our stated according to the authoritarism show of the authors or according to the level of authoritarism of the polítical conjuncture.